2006
DOI: 10.1534/genetics.104.038489
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Population-Dependent Linkage Disequilibrium Detected in an Inbreeding Plant Species, Hordeum vulgare

Abstract: In human genetics a detailed knowledge of linkage disequilibrium (LD) is considered a prerequisite for effective population-based, high-resolution gene mapping and cloning. Similar opportunities exist for plants; however, differences in breeding system and population history need to be considered. Here we report a detailed study of localized LD in different populations of an inbreeding crop species. We measured LD between and within four gene loci within the region surrounding the hardness locus in three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
170
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(188 citation statements)
references
References 42 publications
17
170
1
Order By: Relevance
“…We found limited evidence of breakdown of intrachromosomal LD (Supplementary Figure 2), contrasting with previous findings in both wild barley (Morrell et al, 2005;Caldwell et al, 2006) and barley cultivars (Caldwell et al, 2006) but showing striking similarities to the landrace dataset from Syria and Jordan studied by Caldwell et al (2006). Average intrachromosomal LD was also similar to that reported for landrace barley from Syria and Jordan by Russell et al (2011) but higher than in wild barley from the same area and lower than in a worldwide set of both two-and six-row barley cultivars (Malysheva-Otto et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…We found limited evidence of breakdown of intrachromosomal LD (Supplementary Figure 2), contrasting with previous findings in both wild barley (Morrell et al, 2005;Caldwell et al, 2006) and barley cultivars (Caldwell et al, 2006) but showing striking similarities to the landrace dataset from Syria and Jordan studied by Caldwell et al (2006). Average intrachromosomal LD was also similar to that reported for landrace barley from Syria and Jordan by Russell et al (2011) but higher than in wild barley from the same area and lower than in a worldwide set of both two-and six-row barley cultivars (Malysheva-Otto et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…Taking into account that T. dicoccoides is a selfer, LD decay in Lr10 was very rapid, within 1-2 kb. This LD extent was also found in wild barley, Hordeum spontaneum, a relative of wheat and a selfer as well (Morrell et al 2006;Caldwell et al 2006). Whole genome LD studies in the selfer A. thaliana have shown a longer extent of LD, up to 250 kb (Nordborg et al 2002).…”
Section: Lr10 Diversity Within and Between Populationsmentioning
confidence: 57%
“…LD was rapidly decaying over the first kb in the wild forms while extending over more than 200 kb in elite cultivars (Caldwell et al 2006). In durum wheat (Triticum durum), LD stretches for a long distance (Maccaferri et al 2005), with high LD values found between loci located 50 cM apart.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Caldwell et al 7 described the three hin genes in DNA and amino sequences for over 70 commercial varieties in detail, but failed to identify any of the hin b haplotypes (unpublished http://www.ncbi.nih.gov). However, a number of SNPs on both hin a and hin b alleles have been described in wild accessions (Caldwell et al unpublished).…”
Section: Discussionmentioning
confidence: 99%